Sustainable development education practices in elementary schools - Ganes Gunansyah; Ulhaq Zuhdi; Suprayitno Suprayitno; Manda Rohadatul Aisy (Journal of Education and Learning (EduLearn), 2021)
This study described the practice of Education for Sustainable Development (ESD) along with the supporting factors of the implementation of ESD in three elementary schools (SD) which are referred to as pilot education schools in Surabaya, namely SD Al Irsyad, Citra Berkat Primary Schooland Putat Gede I Surabaya Elementary School. The study used a qualitative approach with comparative descriptive methods. The instrument used in the form of in-depth interviews and documentation studies. Data analysis techniques included data reduction, data presentation and verification. The results of this study indicated that sustainable development practices that have been implemented in the Primary School in Surabaya take place (1) as diverse as conservation which includes the stages of preservation, restoration, adaptation and revitalization and ecoliteracy to facilitate so students can build connections, awareness and experience, (2) has been supported by the commitment of the school community and the leadership of the school principal as outlined in various policies and integrated into curricular and extracurricular activities, and (3) has shown a number of development indicators sustainable in the field of education. Based on the linkages of the three main aspects of ESD, it appears that practices implemented in schools are still dominantly focused on environmental activities. However, there have been efforts to link environmental activities with social and economic activities through entrepreneurship week, cultural appreciation shows and other collaborations and participation that involve the participation of school members, the community and other policy makers even though in a limited scope and simple activities.